2017
DOI: 10.1371/journal.pone.0178446
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative indicator diagram for lytic polysaccharide monooxygenases reveals the role of aromatic surface residues in HjLPMO9A regioselectivity

Abstract: Lytic polysaccharide monooxygenases (LPMOs) have changed our understanding of lignocellulosic degradation dramatically over the last years. These metalloproteins catalyze oxidative cleavage of recalcitrant polysaccharides and can act on the C1 and/or C4 position of glycosidic bonds. Structural data have led to several hypotheses, but we are still a long way from reaching complete understanding of the factors that determine their divergent regioselectivity. Site-directed mutagenesis enables the investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Extensive characterization studies of LPMOs encoded in fungal genomes have revealed that AA9 LPMOs vary in oxidization preference and secondary structure of the substrate-binding surface [18,19,26,27], which has attracted extensive research efforts to unveil structural insights into substrate recognition and catalytic mechanism of LPMOs [5, [32][33][34]49]. Adding to the current knowledge of the substrate interaction of C1specific LPMOs, we propose new insights and hypotheses for binding motifs and for the C1-specificity of HiLPMO9B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive characterization studies of LPMOs encoded in fungal genomes have revealed that AA9 LPMOs vary in oxidization preference and secondary structure of the substrate-binding surface [18,19,26,27], which has attracted extensive research efforts to unveil structural insights into substrate recognition and catalytic mechanism of LPMOs [5, [32][33][34]49]. Adding to the current knowledge of the substrate interaction of C1specific LPMOs, we propose new insights and hypotheses for binding motifs and for the C1-specificity of HiLPMO9B.…”
Section: Discussionmentioning
confidence: 99%
“…However, elucidating LPMO–substrate interactions at the molecular level remains a significant challenge, as the most common AA9 LPMO substrate is insoluble cellulose . Accordingly, previous investigations of LPMO–substrate interactions have focused on LPMOs active on soluble polysaccharides .…”
Section: Introductionmentioning
confidence: 99%
“…The cloning of Pc LPMO9D (Uniprot ID H1AE14), Nc LPMO9C (Q7SHI8), Hj LPMO9A (O14405), all with C‐terminal his 6 ‐tag, was described earlier . All mutants were created using Pfu Ultra High‐Fidelity DNA Polymerase (Agilent), the primers are listed in Tables S1–S4, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…After construct generation in E. coli BL21 (DE3), plasmid DNA was Swa I‐linearized and transformed into freshly prepared electro‐competent P. pastoris CBS7435_MutS cells . Selection of the best producing strain (typically out of 10 transformants) and shake flask LPMO production and purification was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation